2022
DOI: 10.12701/jyms.2022.00101
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of pulsed radiofrequency in reducing pain: a narrative review

Abstract: Pain from nervous or musculoskeletal disorders is one of the most common complaints in clinical practice. Corticosteroids have a high pain-reducing effect, and their injection is generally used to control various types of pain. However, they have various adverse effects including flushing, hyperglycemia, allergic reactions, menstrual changes, immunosuppression, and adrenal suppression. Pulsed radiofrequency (PRF) is known to have a pain-reducing effect similar to that of corticosteroid injection, with nearly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…23 This could possibly be mediated via microscopic changes of the mitochondria, microfilaments, and microtubules in Aδ and C-type fibers. 24 Nonetheless, histologic murine studies have demonstrated only transient changes in the sciatic nerve with PRF, suggesting there may also be non-structural changes in gene expression or cytokine upregulation that are eliciting positive effects. 25 Indeed, PRF has been shown to be associated with downstream changes in gene and molecular expression, such as lower levels of proinflammatory cytokines IL-6 and TNFα, lower levels of intracellular proteins such as β-catenin that are correlated with neuropathic pain, and internalization of glutamate receptor subunits.…”
Section: Mechanisms Of Prf In Ctsmentioning
confidence: 99%
“…23 This could possibly be mediated via microscopic changes of the mitochondria, microfilaments, and microtubules in Aδ and C-type fibers. 24 Nonetheless, histologic murine studies have demonstrated only transient changes in the sciatic nerve with PRF, suggesting there may also be non-structural changes in gene expression or cytokine upregulation that are eliciting positive effects. 25 Indeed, PRF has been shown to be associated with downstream changes in gene and molecular expression, such as lower levels of proinflammatory cytokines IL-6 and TNFα, lower levels of intracellular proteins such as β-catenin that are correlated with neuropathic pain, and internalization of glutamate receptor subunits.…”
Section: Mechanisms Of Prf In Ctsmentioning
confidence: 99%
“…Its mechanism of action is not clear. Current studies have shown that pulsed radiofrequency can exert analgesic effects through long-term inhibition of pain signals transmitted from peripheral nerves to the central nervous system, inactivation of microglia, reduction of pro-inflammatory cytokines, increase of endogenous opioid precursor mRNA, enhancement of descending pain inhibition pathways, inhibition and damage of nociceptive nerve fibers [3].…”
Section: Introductionmentioning
confidence: 99%
“…PRF occurs through RF generators which can produce transient pulsed RF current 8,9 . The RF generator uses alternatively repeated electrical stimulation, maintaining the temperature of the neural tissue below 42°C 10 . In PRF, the short duration and resting phase between pulses can avoid apoptosis and necrosis of histocytes 11 …”
Section: Introductionmentioning
confidence: 99%